2021
DOI: 10.1111/jphd.12486
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the magnitude of oral health inequality over time in Canada and the United States

Abstract: Objectives: To assess the magnitude of, and changes in, absolute and relative oral health inequality in Canada and the United States, from the 1970s till the first decade of the new millennium. Methods: Data were obtained from four national surveys; two Canadian (NCNS 1970-1972 and CHMS 2007-2009 and two American (HANES 1971-1974 and NHANES 2007-2008. The slope and relative index of inequality were used to measure absolute and relative inequality, respectively. Percentage change in inequality was also calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(33 reference statements)
2
6
0
Order By: Relevance
“…The current findings are in line with those from Western countries and Japan [5][6][7] ; education-related oral health inequalities were lower in countries that cover wider dental treatments, high social welfare, or with relatively lower Gini coefficients. [5][6][7] The evidence provided indicates that the trend was similar in Asian countries.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The current findings are in line with those from Western countries and Japan [5][6][7] ; education-related oral health inequalities were lower in countries that cover wider dental treatments, high social welfare, or with relatively lower Gini coefficients. [5][6][7] The evidence provided indicates that the trend was similar in Asian countries.…”
Section: Resultssupporting
confidence: 89%
“…There is empirical evidence of socioeconomic-related oral health inequalities in cross-country comparisons. [5][6][7] Socioeconomic status affects oral health, and socioeconomic inequalities in tooth loss have been observed in older adults. 2 Tooth loss is considered one of the most important indicators of poor oral health in older adults because it reflects their continuing exposure to determinants of oral health, such as socioeconomic status, oral health behaviours and dental treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the results of this study coincide with previous research demonstrating oral health inequality to be worse in the US than in the UK [ 15 ] and Canada [ 16 18 ], we found the prevalence of oral disease was higher in the UK. Although we did not empirically assess the role played by the oral healthcare system in mediating inequality, our findings suggest that the funding and delivery of oral healthcare may potentially contribute to an exacerbation of inequality and warrants future research.…”
Section: Discussionsupporting
confidence: 89%
“…Their study speaks to the more equitable nature of the NHS, shedding light on how differences in the funding and delivery of dental care might impact the distribution of oral health in a country. Previous research comparing oral health inequality between Canada and the US has reported persistent inequality over time in both countries, with a disproportionate burden of oral disease concentrated among the poor, particularly in the US [ 16 18 ]. Despite highly privatised oral health care systems, inequality in the uptake of restorative services was found to decline in both countries, suggestive of enhanced access to dental services over time, which was however inadequate to address the burden of oral disease, particularly among the poor [ 18 ].…”
Section: Introductionmentioning
confidence: 99%